2021
DOI: 10.3389/fpsyg.2021.715301
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Noise on Adolescents’ Executive Function: An Online Study in the Context of Home-Learning During a Pandemic

Abstract: UNICEF estimates that 1.6 billion children across the world have had their education impacted by COVID-19 and have attempted to continue their learning at home. With ample evidence showing a negative impact of noise on academic achievement within schools, the current pre-registered study set out to determine what aspects of the home environment might be affecting these students. Adolescents aged 11–18 took part online, with 129 adolescents included after passing a headphone screening task. They filled out a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…These findings suggest that high home noise levels lead to higher annoyance rates and may hinder home learning affecting both young and adults. A long-term effect of in-home noise on adolescents affects task performance (Chere & Kirkham, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that high home noise levels lead to higher annoyance rates and may hinder home learning affecting both young and adults. A long-term effect of in-home noise on adolescents affects task performance (Chere & Kirkham, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Having been constantly exposed to a noisy home significantly negatively affected performance on tasks involving executive functions [41] .  Socioeconomic level of the family.…”
Section: Family Supportmentioning
confidence: 99%
“…However, a systematic investigation of the associations between children’s living environment, attentional resources and noise sensitivity is needed. Indeed, research on adolescents has revealed complex interactions between participants’ age, their living environment and their performance at an attentional inhibitory control task [ 73 ].…”
Section: General Conclusion and Suggestions For Future Researchmentioning
confidence: 99%